2020
DOI: 10.1002/pen.25344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organo‐Modified Montmorillonite on the Morphology and Properties of SEBS/TPU Nanocomposites

Abstract: In this study, novel polystyrene‐b‐poly(ethylene‐butylene)‐b‐polystyrene (SEBS)/thermoplastic polyurethane (TPU)/organo‐modified montmorillonites (OMMT) nanocomposites were prepared by melt mixing. Three different organo‐modified montmorillonites, DK2, DK3, and DK4 (listed in descending order of hydrophilicity) were selected. The compatibilizing and reinforcing effects of OMMT on the structure, morphology, thermal stability, mechanical and rheological properties of the SEBS/TPU blends were studied. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The hard segments (HS) of TPU are typically derived from diisocyanates and small molecule chain extenders (such as diamines or diols), which endow them with good mechanical strength [4,5], whereas the soft segments (SS) are formed by oligomeric diols and provide them flexibility and elastic behavior [6][7][8]. Therefore, the material properties can be customized by controlling the ratio of soft and hard segments and structural morphologies [9][10][11], which enable their unique performance, such as excellent wear resistance, high tensile strength, good chemical resistance, and machinability [12,13]. In recent years, TPU play an increasingly important role in many industrial fields, especially in the extensive applications of replacing traditional thermoset elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…The hard segments (HS) of TPU are typically derived from diisocyanates and small molecule chain extenders (such as diamines or diols), which endow them with good mechanical strength [4,5], whereas the soft segments (SS) are formed by oligomeric diols and provide them flexibility and elastic behavior [6][7][8]. Therefore, the material properties can be customized by controlling the ratio of soft and hard segments and structural morphologies [9][10][11], which enable their unique performance, such as excellent wear resistance, high tensile strength, good chemical resistance, and machinability [12,13]. In recent years, TPU play an increasingly important role in many industrial fields, especially in the extensive applications of replacing traditional thermoset elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the addition of nanoclay into the PU matrix improves the tensile properties to a significant degree [65]. As an example, adding 10 wt.% of modified clay increases the tensile strength, modulus, and strain at the break by more than 100% [45,56]. Young's modulus of the nanoclay-TPU nanocomposites has previously been seen to increase with the addition of modified nanoclays [66].…”
Section: Mechanical Properties Of Nanofiller-tpu Nanocompositesmentioning
confidence: 99%
“…Several researchers have addressed that blending TPU with nanomaterials enhances its physical properties and toughness [44]. The TPU's good compatibility with polycarbonate or acrylonitrile butadiene styrene was behind using TPU as a modifier to create new blends [45]. The effect of using special additives can be seen in creating properties necessary to achieve flame retardance, antistatic, and radiation crosslinking ability [46].…”
Section: Thermoplastic Polyurethane Compositementioning
confidence: 99%
“…The increase of G 0 and G 00 is basically greater for PUC/OMMT nanocomposites when compared to their neat PUC/75 counterparts due to the state of the better filler-polymer bonding and particle-particle interactions. 47,48 This could be an effect of the OMMT-PUC interfacial interaction, homogeneity dispersion, and larger surface area of clay particles exposed to the polymer chains. 5 The low frequency region of the rheological curve indicates the intercalated effect of OMMT on the G 0 and G 00 of PUC/OMMT nanocomposites in comparison with G 0 and G 00 of neat PUC/75.…”
Section: Dynamic Frequencymentioning
confidence: 99%
“…As can be observed; a substantial reduction in viscosity is clearly illustated with increasing shear rate. 47 The effect of the nanoclay network on the mobility restriction of PUC/75 chains appears visibly and thus resists the flow of the melted segments of PUC/75. This can reveal the shear-thinning behaviour that is strongly induced by 3-D nanoclay structural network.…”
Section: Dynamic Frequencymentioning
confidence: 99%